The impact of psychological transformation game “My Dao” on value orientations of participants - Melnyk, Yu. B.; Мельник, Ю. Б.; Stadnik, A. V.; Стаднік, А. В. (International Journal of Science Annals. - 2021. - Vol. 4, № 2. - P. 21-29, 2021)
Ігри психологічної трансформації, які мають великий потенціал для вирішення широкого кола проблем, пов'язаних з психічним здоров'ям клієнтів, стають дедалі популярнішими серед психологів та психотерапевтів. Ці методики повинні бути не лише цікавими та привабливими для клієнтів, але й ефективними як форма психологічної практики. Мета дослідження: дослідити вплив гри психологічної трансформації «Моє Дао» на ціннісні орієнтації учасників за допомогою діагностичного методу Шварца.

Psychological transformation games that have great potential for solving a wide range of problems related to clients’ mental health are becoming increasingly popular among psychologists and psychotherapists. These techniques should be not only interesting and attractive to clients but also effective as a form of psychological practice. The aim of the study: to investigate the impact of the psychological transformation game “My Dao” on value orientations of participants using the diagnostic method of Schwartz. Material and Methods: The study used the toolkit of the psychological transformation game “My Dao”. The effectiveness of the game impact on the participants was determined by means of the diagnostics of value orientations suggested by Schwartz. The treatment group consisted of 134 people, 75 men (55.97%) and 59 women (44.03%) aged 17-35 years. The control group included 126 people, 69 men (54.76%) and 57 women (45.24%) aged 18-30 years. The results of the treatment and control groups were measured using the SPSS Statistics Module. The obtained results prove statistical significance (p<0.05). Results: The greatest impact of the developed game on the participants is observed at the level of normative ideals: tradition, conformity, security, hedonism and universalism. This indicates their certain change towards increasing harmony and stability, as well as reducing humility and acceptance of their destiny. At the level of individual priorities, there is an increase in hedonism, power and stimulation, which indicates an increase in the role of satisfaction, success, ambition, the desire for novelty and strong emotions. The obtained high results of universalism, hedonism, self-direction and conformity indicate an increase in understanding, tolerance, enjoyment of life, self-control, self-government, self-discipline and politeness of game participants. Conclusions: The use of the transformation game “My Dao” in psychological practice is an effective psychotherapeutic method that affects the value orientations of participants, changes in self-esteem and motivation, disclosure of their personal resources to solve problems and develop further. This technique is universal due to the age category of participants and the ability to solve psychological problems.
Keywords: psychological transformation game; game “My Dao”; value orientations; motivation; diagnostics; гра психологічної трансформації; psychological problems; toolkit; ціннісні орієнтації; мотивація; діагностика; інструментарій; психологічні проблеми